Automorphisms and isomorphisms of Jha-Johnson semifields obtained from skew polynomial rings - Brown, Christian; Pumpluen, Susanne; Steele, Andrew (Taylor & Francis, 2018)
We study the automorphisms of Jha-Johnson semifields obtained from a right invariant irreducible twisted polynomial f Є K[t;σ], where K = Fqn is a finite field and σ an automorphism of K of order n, with a particular emphasis on inner automorphisms and the automorphisms of Sandler and Hughes-Kleinfeld semifields. We include the automorphisms of some Knuth semifields (which do not arise from skew polynomial rings). Isomorphism between Jha-Johnson semifields are considered as well.